PP31 Medical Device Regulation: What Is New? - Oelze, Ilse-Barbara; Neeser, Kurt; Müller, Elvira (International journal of technology assessment in health care, 2019)
Copyright © Cambridge University Press 20192019Cambridge University PressIntroductionIn 2017, the European Union (EU) commission released the final versions of the Medical Device Regulation (MDR) and In-vitro Diagnostic Device Regulation. These regulations will replace the EU directives (Medical Device Directive [MDD], In-vitro Diagnostic Device [IVDD], and Active Implantable Medical Device [AIMD]). EU regulations are effective in all EU countries at date of publication. In contrast, the EU directives must be implemented in national law first.MethodsGuidelines and respective legislation, consultation results and methods/medical device (MD) evaluations were reviewed and analyzed. Decision criteria and reasoning, assessment outcomes and potential impact on price negotiations were the main aspects for comparison.ResultsManufacturers have to be aware of the importance of clinical data for demonstrating the compliance of their products. This applies both to the approval of the products and the “post-market activities” and particularly to the “post-market clinical follow-up” for which requirements for Class I and II products need to be further developed. The MDR requires manufacturers to collect clinical data before and after approval, which could lead to excessive documentation requirements. The term “sufficient clinical data” from the MDR is unclear. A functional Eudamed specification is necessary, which enables an automated processing of relevant data. A stronger involvement in the evaluation process is needed as well as more transparency in the Joint Federal Committee (G-BA) and faster evaluation processes.ConclusionsThe MDR increases the burden especially for small businesses, and it is doubtable that the ultimate goal – improving patient safety – will be achieved. The increased demands and rising costs of the new EU MDR and bottlenecks at Notified Bodies can be a risk for the MD industry. Due to the general reduction in the remuneration for services with a high proportion of technical services, it is feared that products will be withdrawn from the market for economic reasons or that they will not be marketed.